Certain Related Factors Concerning Elder Prosthesis Rehabilitation in Cau Giay District, Hanoi City - Dung, Dao Thi; Son, Tran Ngoc (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2017)
Elder dental health care get more and more attention, especially tooth loss and prosthesis status. Elder prosthesis rehabilitation is extremely important. It improves directly their quality of life. Our Objective of the study is valuation of certain related factors concerning elder prosthesis rehabilitation in Cau Giay District, Hanoi city.  Research methods is cross-sectional study. we realize dental examination for 160 seniors, and select the subjects who have tooth loss and wear dental prosthetics. Our researched  Results: as high educational level as high proportion of prosthodontic treatment. Manual workers with low income have less prosthodontic therapy than intellectual workers. Communicated occupation have high percentage of prosthodontics. Dental prosthetic care Location: mostly in private clinics then hospitals. As long time of wearing dental prosthesis as low quality of prosthetics, as low patient’s satisfaction about aesthetic as well as chewing capacity. Keyword Factors related to prosthodontics References [1] Hoàng Tử Hùng, “Tích tuổi và tình trạng răng miệng”, Thông tin Y Dược học, Sở Y tế TP Hồ Chí Minh, tập IX, (2002) 37. [2] Bộ môn Nha Cộng Đồng Viện đào tạo RHM - Đại học Y Hà Nội, "Nghiên cứu thực trạng và nhu cầu điều trị bệnh răng miệng ở người cao tuổi Việt Nam", Đề tài cấp Bộ(2014) 5. [3] Chu Đức Toàn, “Nghiên cứu thực trạng mất răng và nhu cầu điều trị của người cao tuổi tại quận Đống Đa - Hà Nội”, Luận văn thạc sỹ y học, Trường Đại học Y Hà Nội, (2012) 52. [4] Trương Mạnh Dũng, "Tình trạng mất răng ở người cao tuổi phường Nghĩa Tân, quận Cầu Giấy, thành phố Hà Nội", Tạp chí y học thực hành. 686(11), (2007) 5. [5] Nguyễn Văn Bài, “Góp phần đánh giá tình trạng mất răng và nhu cầu điều trị phục hình ở một số tỉnh phía Bắc”, Luận văn chuyên khoa II, Trường Đại học Y Hà Nội, (1994) 16. [6] Phạm Văn Việt, “Nghiên cứu tình trạng, nhu cầu chăm sóc sức khỏe răng miệng và đánh giá kết quả hai năm thực hiện nội dung chăm sóc răng miệng ban đầu ở người cao tuổi tại Hà Nội”, Luận án tiến sĩ y học, Đại học Y Hà Nội, (2004) 14.